Revealing the mechanism of stress generation for construction frontline professionals through development of structural stressors–coping–stress models. (June 2022) - Liang, Qi; Zhou, Zhiyuan; Li, Xiaoyue; Hu, Qijun; Ye, Gui
Highlights: Use mixed methods to examine how coping strategies mediate the influence of the stressors on the stress of construction frontline professionals. Development of structural Stressors–Coping–Stress models for better understanding the stress issues of construction frontline professionals. Reveal the mechanism of the stressors–stress interactions for employees in the stressful construction industry. Abstract: Construction industry is stressful for its participants. Construction frontline professionals are directly responsible for construction tasks on-site, and their stress management is of critical importance to the project success. Coping strategies could significantly affect stress, while the influence of various coping strategies on stressors–stress interactions for frontline professionals was unclear. Current study sets to examine the mediating effect of two groups of coping strategies on the relationships between stressors and stress. Over 500 valid quantitative data were applied to statistical analyses including confirmatory factor analysis and structural equation modeling (SEM). A final Stressors–Coping–Stress model was developed, which shows: 1) three problem-focused but only one emotion-focused coping strategies can mediate the stressors–stress interactions for frontline professionals; 2) three problem-focused copings, namely cognitive reappraisal, planful problem-solving and instrumental support, are promoted when they have job control, leading to reduced emotional stress; 3) planful problem-solving and instrumental support could mediate the influence of supervisor support on stress, but interestingly, mediating effect of instrumental support on supervisor support–stress interaction causes exacerbated physical stress; 4) the avoidance coping could be restrained by supervisor support but invoked by work overload, imposing different influence on their stress. Practical recommendations were made to improve stress management practices, including realistic workload planning, training for adaptive coping, provision of counselling services, etc. Through revealing the stressors–coping–stress interactions, this study contributed to enhance current understanding of stress management knowledge and improve existing strategies and practices regarding occupational health and safety in the construction industry.